Luminescent properties of Ce³⁺ ions in alkaline earth borophosphates - Dotsenko, V.P.; Berezovskaya, I.V.; Efryushina, N.P.; Voloshinovskii, A.S.; Eijk, C.W.E. van; Dorenbos, P.; Sidorenko, A. (Functional Materials, 2005)
The luminescence properties of Се³⁺ ions in alkaline earth borophosphates МВРО₅ (М - Sr, Ва) have been studied upon excitation in the 3.5-15 eV region. It has been shown that the splitting of the Се³⁺ 5d configuration due to crystal field in МВРО₅ (М - Sr, Ва) is relatively large, nevertheless, the lowest 5d state of Се³⁺ is at a relatively high energy due to the high degree of ionicity of the М-О bond. Comparison of the luminescence excitation spectra for МВРО₅:Се³⁺ (М - Са, Sr, Ва) indicates that the fundamental absorption band of these host lattices is due to transitions within anionic groups.